Lithium ion battery Si / C negative electrode aqueous binder and preparation method thereof
By bonding the cationic aqueous polyurethane emulsion with the polyacrylic acid aqueous solution, a polyacrylic cationic aqueous polyurethane binder was prepared, which solved the problem of electrode structure collapse caused by volume changes in silicon-based anode materials in lithium-ion batteries, achieved efficient self-repair and mechanical properties, and significantly improved the cyclic stability and Coulomb efficiency of the battery.
Patent Information
- Application Number
- CN202411716125.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-03-07
Smart Images

Figure CN119570428A_ABST
Abstract
Description
Technical field:
[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a lithium ion battery Si / C negative electrode aqueous binder and a preparation method thereof. Background technology:
[0002] Silicon-based negative electrodes have many advantages such as high theoretical specific capacity, low operating voltage and abundant reserves, and are expected to become one of the preferred negative electrode materials for the next generation of high energy density lithium-ion batteries. However, due to the material's own factors, the stress effect caused by the huge volume change (expansion rate > 300%) of silicon negative electrode materials during the charge and discharge process leads to the collapse of the electrode structure, which seriously affects the cycle life of silicon-based negative electrodes.
[0003] Currently commercialized polyvinylidene fluoride (PVDF) is widely used as a binder for lithium-ion batteries (LIBs) due to its wide operating potential, high electrochemical stability, and good adhesion to aluminum and copper current collectors. However, its surface lacks polar functional groups such as -OH and -COOH, and only weak van der Waals forces exist when it interacts with silicon active substances. This force is not enough to make silicon particles adhere firmly to the surface of the current collector. Even under the smallest mechanical stress, PVDF binders cannot suppress excessive volume expansion and cannot provide sufficient adhesion for silicon particles. In addition, PVDF binders also require N-methylpyrrolidone (NMP) as a solvent, which is toxic and harmful to the environment.
[0004] Polyacrylic acid (PAA) contains a large number of carboxyl groups in its molecular chain, which can form strong hydrogen bonds with the silicon surface and has been proven to be an ideal binder for high-capacity silicon-based negative electrode materials. Considering the demand for capacity in practical applications and commercial production processes, the PAA system is more likely to achieve high-capacity performance of lithium-ion batteries when used as a silicon negative electrode binder. However, the chain rigidity and relatively high glass transition temperature of the PAA polymer limit the elasticity of amorphous PAA. Therefore, it is necessary to modify PAA by chemical or physical means to increase its elasticity and chain mobility in order to cope with the huge volume changes of silicon during charging and discharging, and to achieve self-healing function, thereby stabilizing the electrode structure and even repairing the mechanically broken interface, thereby maintaining the integrity of the electrode structure. Summary of the invention:
[0005] The present invention solves the problems existing in the prior art and provides a lithium ion battery Si / C negative electrode aqueous binder and a preparation method thereof. The binder provided by the present invention is obtained by bonding a cationic aqueous polyurethane emulsion with a thermally reversible self-repairing function with a polyacrylic acid aqueous solution through hydrogen bonds, ionic bonds and covalent ester bonds. The polyurethane component provides the self-repairing property and high elasticity of the binder, and the polyacrylic acid component provides the rigidity of the binder. The aqueous binder has excellent bonding force and mechanical properties, can effectively inhibit the expansion of negative electrode silicon-based particles, and maintain the integrity of the electrode structure.
[0006] The first object of the present invention is to provide a lithium ion battery Si / C negative electrode aqueous binder, wherein the lithium ion battery Si / C negative electrode aqueous binder is a polyacrylic acid-based cationic waterborne polyurethane binder, which is formed by bonding a cationic waterborne polyurethane emulsion with a thermally reversible self-healing function to a polyacrylic acid aqueous solution through hydrogen bonds, ionic bonds and covalent ester bonds, and the mass ratio of polyurethane to polyacrylic acid is 15:1 to 4:1.
[0007] The second object of the present invention is to provide a method for preparing the lithium ion battery Si / C negative electrode aqueous binder, comprising the following steps:
[0008] (1) In an inert atmosphere, polytetrahydrofuran (PTMG) is prepolymerized with two different aliphatic isocyanates at 70°C to 85°C for 1 to 2 hours, one aliphatic isocyanate is isophorone diisocyanate (IPDI), the other aliphatic isocyanate is hexamethylene diisocyanate (HDI) or dicyclohexylmethane diisocyanate (HMDI), and the molar ratio (R value) of isocyanate (NCO) to hydroxyl (OH) is 1.1 to 1.4;
[0009] (2) After cooling the prepolymerization system of step (1) to 38° C. to 42° C., cationic chain extender N-methyldiethanolamine (MDEA) is added dropwise, with the molar ratio of N-methyldiethanolamine to polytetrahydrofuran being 0.9 to 1.1:1. After the addition is complete, the temperature is raised to 80° C. to 90° C., and the reaction is continued for 1 to 2 hours. Dimethylglyoxime (DMG) and acetone are added, with the molar ratio of dimethylglyoxime to polytetrahydrofuran being 0.9 to 1.1:1, and the reaction is continued for 3 to 4 hours;
[0010] (3) The reaction system obtained in step (2) was cooled to 45°C to 55°C, acetone was removed, and then an aqueous solution of polyacrylic acid and deionized water were added and stirred. 0.9×10 4 ~1.1×10 4 r min -1 Emulsification is carried out at a rotation speed of 10 to 20 minutes to obtain a polyacrylic acid-based cationic water-based polyurethane adhesive.
[0011] The hydroxyl group in step (1) includes OH of polytetrahydrofuran and OH of cationic chain extender dimethylglyoxime. The above molar ratio (R value) of isocyanate (NCO) to hydroxyl (OH) refers to the molar ratio of NCO to OH in the entire reaction system.
[0012] Preferably, the number average molecular weight of the polytetrahydrofuran in step (1) is 950-1050 g / mol. More preferably, the number average molecular weight of the polytetrahydrofuran in step (1) is 1000 or 2000 g / mol.
[0013] Preferably, in step (1), the molar ratio of isophorone diisocyanate to another aliphatic isocyanate is 6:1 to 2:1.
[0014] Preferably, the specific steps of step (2) are as follows: after cooling the prepolymerization system of step (1) to 40°C, dropwise adding cationic chain extender N-methyldiethanolamine, the molar ratio of N-methyldiethanolamine to polytetrahydrofuran is 1:1, heating to 85°C after the addition is complete, continuing the reaction for 1 to 2 hours, adding dimethylglyoxime and acetone, the molar ratio of dimethylglyoxime to polytetrahydrofuran is 1:1, and continuing the reaction for 3 to 4 hours. Acetone is used to adjust the viscosity of the system, and there is no specific limitation on the viscosity of the system, as long as the system stirrer can be stirred normally.
[0015] Preferably, the viscosity-average molecular weight of the polyacrylic acid in step (3) is 450,000, 1.25 million or 4 million.
[0016] The specific steps of step (3) are as follows: the system is cooled to 50°C, acetone is removed by rotary evaporation at 45°C to 50°C, and then an aqueous solution of polyacrylic acid (PAA) and an appropriate amount of deionized water are added, stirred for 30 minutes, and a homogenizer is used to mix the mixture at 1×10 4 r min -1 Emulsification is carried out at a rotation speed of 10 to 20 minutes to obtain a polyacrylic acid-based cationic water-based polyurethane adhesive.
[0017] Polyacrylic acid is easily soluble in water. The present invention does not impose any specific limitation on the concentration of the polyacrylic acid aqueous solution, as long as the polyacrylic acid is completely dissolved in water.
[0018] Preferably, the pH of the polyacrylic acid-based cationic waterborne polyurethane binder system obtained in step (3) is 5-6.
[0019] The third object of the present invention is to provide the use of the lithium ion battery negative electrode aqueous binder in a lithium ion battery.
[0020] The fourth object of the present invention is to provide a lithium ion battery, wherein the negative electrode material is Si / C, and the negative electrode material is bonded by the lithium ion battery negative electrode aqueous binder.
[0021] Compared with the prior art, the present invention has the following advantages:
[0022] (1) The present invention bonds a water-based polyurethane emulsion with thermally reversible self-healing and high elasticity with a rigid polyacrylic acid aqueous solution through hydrogen bonds, ionic bonds and covalent ester bonds to prepare a novel polyacrylic acid-based cationic water-based polyurethane binder system. At the same time, the binder is endowed with excellent self-healing and bonding properties, which can effectively inhibit the expansion of negative electrode silicon-based particles during the charging and discharging process, maintain the stability of the electrode structure, and has excellent first coulomb efficiency and good battery cycle stability.
[0023] (2) The present invention uses water as a dispersant to prepare an aqueous binder system, which is simple to prepare. When producing electrodes, the aqueous solvent can evaporate and dry quickly, which is environmentally friendly and pollution-free. Description of the drawings:
[0024] Figure 1 Schematic diagram of the structure of the adhesive obtained in Example 1 or 3 of the present invention.
[0025] Figure 2 This is the infrared spectrum of the adhesive obtained in Example 3 of the present invention.
[0026] Figure 3 This is a photo of the thermally reversible self-healing process of the adhesive obtained in Example 2 of the present invention.
[0027] Figure 4 The tensile properties of the adhesive obtained in Example 2 of the present invention before and after self-repair, wherein the green line represents the original tensile properties of the film, and the red line represents the tensile properties after self-repair. Specific implementation method:
[0028] The following examples are provided to further illustrate the present invention, rather than to limit the present invention.
[0029] Unless otherwise defined, all professional terms used hereinafter have the same meaning as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specified, the experimental materials and reagents herein are conventional commercial products in the art.
[0030] Example 1
[0031] Under nitrogen atmosphere, polytetrahydrofuran PTMG (Mn = 1000g / mol, 0.04mol), isophorone diisocyanate IPDI (0.109mol), dicyclohexylmethane diisocyanate HMDI (0.023mol) were added to a three-necked reaction bottle equipped with a condenser, a magnetic stirrer, and a thermometer, and the oil bath was turned on and heated to 80°C for 1.5 hours of prepolymerization. After the system was cooled to 40°C, cationic chain extender N-methyldiethanolamine MDEA (0.04mol) was added dropwise, and stirring was continued for 1.5 hours after the addition was completed. Then, dimethylglyoxime DMG (0.04mol) and an appropriate amount of acetone (10mL) were added to adjust the viscosity of the system, and the reaction was continued for 4 hours. After the reaction, the system was cooled to 50°C, and the acetone was removed by rotary evaporation at 50°C under reduced pressure. Then, polyacrylic acid PAA (molecular weight 1.25 million, 13 g) aqueous solution and an appropriate amount of deionized water were added and stirred for 30 minutes. 4 r min -1 The mixture was emulsified at a rotation speed of 100 for 15 minutes to obtain a polyacrylic acid-based cationic waterborne polyurethane binder 1.
[0032] Example 2
[0033] Under nitrogen atmosphere, polytetrahydrofuran PTMG (Mn = 2000g / mol, 0.04mol), isophorone diisocyanate IPDI (0.109mol), hexamethylene diisocyanate HDI (0.034mol) were added to a three-necked reaction bottle equipped with a condenser, a magnetic stirrer, and a thermometer, and the oil bath was turned on and heated to 70°C for 1 hour for prepolymerization. After the system was cooled to 40°C, cationic chain extender N-methyldiethanolamine MDEA (0.04mol) was added dropwise, and stirring was continued for 1 hour after the addition was completed. Then, dimethylglyoxime DMG (0.04mol) and an appropriate amount of acetone (20mL) were added to adjust the viscosity of the system, and the reaction was continued for 3 hours. After the reaction, the system was cooled to 50°C, and the acetone was removed by rotary evaporation at 50°C under reduced pressure. Then, an aqueous solution of polyacrylic acid PAA (molecular weight 450,000, 18 g) and an appropriate amount of deionized water were added and stirred for 30 minutes. The mixture was homogenized at 1×10 4 r min -1 The mixture was emulsified at a rotation speed of 10 minutes to obtain a polyacrylic acid-based cationic waterborne polyurethane binder 2.
[0034] Example 3
[0035] Under nitrogen atmosphere, polytetrahydrofuran PTMG (Mn = 1000g / mol, 0.04mol), isophorone diisocyanate IPDI (0.109mol), dicyclohexylmethane diisocyanate HMDI (0.054mol) were added to a three-necked reaction bottle equipped with a condenser, a magnetic stirrer, and a thermometer, and the oil bath was turned on and heated to 85°C for 2 hours of prepolymerization. After the system was cooled to 40°C, cationic chain extender N-methyldiethanolamine MDEA (0.04mol) was added dropwise, and stirring was continued for 2 hours after the addition was completed. Then, dimethylglyoxime DMG (0.04mol) and an appropriate amount of acetone (15mL) were added to adjust the viscosity of the system, and the reaction was continued for 3.5 hours. After the reaction, the system was cooled to 50°C, and the acetone was removed by rotary evaporation at 50°C under reduced pressure. Then, an aqueous solution of polyacrylic acid PAA (molecular weight 4 million, 6 g) and an appropriate amount of deionized water were added and stirred for 30 minutes. 4 r min -1 The mixture was emulsified at a rotation speed of 20 minutes to obtain a polyacrylic acid-based cationic waterborne polyurethane binder 3.
[0036] Example 4
[0037] Under nitrogen atmosphere, polytetrahydrofuran PTMEG (Mn = 1000g / mol, 0.04mol), isophorone diisocyanate IPDI (0.109mol), dicyclohexylmethane diisocyanate HMDI (0.018mol) were added to a three-necked reaction bottle equipped with a condenser, a magnetic stirrer, and a thermometer, and the oil bath was turned on and heated to 80°C for 2 hours of prepolymerization. After the system was cooled to 40°C, cationic chain extender N-methyldiethanolamine MDEA (0.04mol) was added dropwise, and stirring was continued for 2 hours after the addition was completed. Then, dimethylglyoxime DMG (0.04mol) and an appropriate amount of acetone (10mL) were added to adjust the viscosity of the system, and the reaction was continued for 3 hours. After the reaction, the system was cooled to 50°C, and the acetone was removed by rotary evaporation at 50°C under reduced pressure. Then, polyacrylic acid PAA (molecular weight 1.25 million, 10 g) aqueous solution and an appropriate amount of deionized water were added and stirred for 30 minutes. 4 r min -1 The mixture was emulsified at a rotation speed of 10 minutes to obtain a polyacrylic acid-based cationic waterborne polyurethane binder 4.
[0038] Coat the polyacrylic acid-based cationic waterborne polyurethane binder 1-4 emulsion on a polytetrafluoroethylene plate, dry it into a film at room temperature, and then put it into an 80°C forced air drying oven to dry until the mass no longer changes. The self-healing properties of the film are tested by a scratch recovery test. A smooth film of half thickness (0.1 mm) is scratched with a clean blade to test its self-healing properties at 120°C. The microscopic self-healing behavior of the film is observed under an optical microscope, and the tensile properties of the film samples before and after healing are tested. The self-healing rate is defined as the ratio of the tensile strength of the repaired sample to the original sample. The self-healing rates of Examples 1-4 are shown in Table 1.
[0039] Table 1
[0040] sample Self-repair rate Example 1 96% Example 2 95% Example 3 98% Example 4 96%
[0041] From the self-healing test results of Examples 1-4, it can be seen that the polyacrylic acid-based cationic waterborne polyurethane films all have excellent self-healing properties, with a self-healing rate of ≥95%. The scratches on the films prepared in Examples 1-4 have obviously disappeared within 10 minutes at a temperature of 100°C.
[0042] The lithium-ion battery negative electrode aqueous binder obtained in Examples 1-4 was mixed with the conductive agent Super-P and the active material Si / C to prepare a slurry, and the slurry was dispersed at high speed to prepare a negative electrode slurry. The negative electrode slurry was scraped on a copper foil with a four-sided wet film preparation device with a depth of 100 μm. The copper foil was dried at room temperature and then vacuum dried at 120° C. to obtain negative electrode sheets 1-4.
[0043] Example 5
[0044] The slurry is prepared according to the mass ratio of active material Si / C: Super P: polyacrylic acid-based cationic water-based polyurethane binder 1 = 8:1:1. After adding an appropriate amount of deionized water, stir at high speed to make the slurry evenly dispersed. The solid content of the slurry is 45%-48%. Then use a coater to coat the slurry on the copper foil with a coating thickness of 80μm. After coating, put it in a vacuum drying oven at 120°C and dry it for 12 hours to obtain the pole piece 1. The pole piece 1 is cut and then covered with a 20mm wide 3M tape. Cut out a long strip with a fixed width and stretch at a constant speed of 50mm / min. The force to separate the tape and the copper foil during the test is the peeling force.
[0045] The half-cell was assembled in the order of negative electrode shell, lithium sheet, diaphragm, electrolyte, electrode sheet 1, steel sheet, spring sheet, and positive electrode shell, and the electrochemical performance test was performed.
[0046] Example 6
[0047] The same as Example 5, except that the aqueous polyurethane binder used is polyacrylic acid-based cationic aqueous polyurethane binder 2.
[0048] Example 7
[0049] The same as Example 5, except that the aqueous polyurethane binder used is polyacrylic acid-based cationic aqueous polyurethane binder 3.
[0050] Example 8
[0051] The same as Example 5, except that the aqueous polyurethane binder used is polyacrylic acid-based cationic aqueous polyurethane binder 4.
[0052] Comparative Example 1
[0053] Same as Example 5, except that the binder is PAA (M v =1.25 million).
[0054] Comparative Example 2
[0055] The same as Example 5, except that the binder is aqueous polyurethane emulsion 1, and the preparation method of the emulsion is as follows:
[0056] Under nitrogen atmosphere, polytetrahydrofuran PTMEG (0.04 mol), isophorone diisocyanate IPDI (0.109 mol), and dicyclohexylmethane diisocyanate HMDI (0.023 mol) were added to a three-necked reaction bottle equipped with a condenser, a magnetic stirrer, and a thermometer, and the oil bath was turned on and heated to 80°C for 1.5 hours of prepolymerization. After the system was cooled to 40°C, the cationic chain extender N-methyldiethanolamine MDEA (0.04 mol) was added dropwise, and stirring was continued for 1.5 hours after the addition was completed. Then, dimethylglyoxime DMG (0.04 mol) and an appropriate amount of acetone (10 mL) were added to adjust the viscosity of the system, and the reaction was continued for 4 hours. After the reaction was completed, the system was cooled to 50°C, and the acetone was removed by vacuum rotary evaporation at 50°C using a rotary evaporator, and then glacial acetic acid (0.04 mmol) and an appropriate amount of deionized water were added, stirred for 30 minutes, and a homogenizer was used at 1×10 4 r min -1 The mixture was emulsified at a rotation speed of 100 for 15 minutes to obtain a water-based polyurethane emulsion binder 1.
[0057] Comparative Example 3
[0058] The test results of Example 2 disclosed in patent CN 118185517A.
[0059] The peeling force and electrochemical performance test results of Examples 5-8 and Comparative Examples 1-3 are shown in Table 2:
[0060] Table 2
[0061]
[0062]
[0063] The coulombic efficiencies of 100 cycles of Example 5 and Example 7 at different current densities are shown in Table 3:
[0064] Table 3
[0065] Current density Example 5 Example 7 50mA / g 99.41% 99.44% 100mA / g 99.42% 99.59% 200mA / g 99.51% 99.92% 500mA / g 99.78% 99.93% 1000mA / g 99.92% 99.98%
[0066] From the above results, it can be seen that the polyacrylic acid-based cationic water-based polyurethane emulsion of the present invention is not only environmentally friendly and pollution-free, but also has excellent bonding properties and self-healing properties. The composite film has excellent elastic properties, and the elongation at break before and after self-healing is close to 1000%. The half-cells prepared by Examples 5-8 have a high first coulombic efficiency (ICE ≥ 90.5%), and also have good cycle performance, with a capacity retention rate of more than 99% after 100 cycles. In Comparative Example 3, at a current density of 1C, the capacity retention rate after 100 cycles is only 66.91%.
[0067] The description of the above embodiments is only used to help understand the technical solution and core ideas of the present invention. It should be pointed out that for technicians in this technical field, several improvements and modifications can be made to the present invention without departing from the principles of the present invention. These improvements and modifications also fall within the scope of protection of the claims of the present invention.
Claims
1. A lithium ion battery Si / C negative electrode aqueous binder, characterized in that: The lithium-ion battery Si / C negative electrode aqueous binder is a polyacrylic acid-based cationic aqueous polyurethane binder, which is formed by bonding a cationic aqueous polyurethane emulsion with a thermally reversible self-healing function to a polyacrylic acid aqueous solution through hydrogen bonds, ionic bonds and covalent ester bonds, and the mass ratio of polyurethane to polyacrylic acid is 15:1 to 4:
1.
2. The method for preparing the aqueous binder for Si / C negative electrode of lithium ion battery according to claim 1, characterized in that: The following steps are involved: (1) in an inert atmosphere, prepolymerizing polytetrahydrofuran with two different aliphatic isocyanates at 70° C. to 85° C. for 1 to 2 hours, wherein one aliphatic isocyanate is isophorone diisocyanate, and the other aliphatic isocyanate is hexamethylene diisocyanate or dicyclohexylmethane diisocyanate, and the molar ratio of isocyanate to hydroxyl is 1.1 to 1.4; (2) After the prepolymerization system of step (1) is cooled to 38° C. to 42° C., a cationic chain extender N-methyldiethanolamine is added dropwise, and the molar ratio of N-methyldiethanolamine to polytetrahydrofuran is 0.9 to 1.1:
1. After the addition is completed, the temperature is raised to 80° C. to 90° C., and the reaction is continued for 1 to 2 hours. Dimethylglyoxime and acetone are added, and the molar ratio of dimethylglyoxime to polytetrahydrofuran is 0.9 to 1.1:1, and the reaction is continued for 3 to 4 hours; (3) The reaction system obtained in step (2) was cooled to 45°C to 55°C, acetone was removed, and then an aqueous solution of polyacrylic acid and deionized water were added and stirred. 0.9×10 4 ~1.1×10 4 r min -1 Emulsification is carried out at a rotation speed of 10 to 20 minutes to obtain a polyacrylic acid-based cationic water-based polyurethane adhesive.
3. The preparation method according to claim 2, characterized in that: The number average molecular weight of the polytetrahydrofuran in step (1) is 1000 or 2000 g / mol.
4. The preparation method according to claim 2 or 3, characterized in that: In step (1), the molar ratio of isophorone diisocyanate to another aliphatic isocyanate is 6:1 to 2:
1.
5. The preparation method according to claim 2, characterized in that: The specific steps of step (2) are as follows: after cooling the prepolymerization system of step (1) to 40° C., dropwise adding cationic chain extender N-methyldiethanolamine, wherein the molar ratio of N-methyldiethanolamine to polytetrahydrofuran is 1:1; after completion of the dropwise addition, heating to 85° C., continuing the reaction for 1 to 2 hours, adding dimethylglyoxime and acetone, wherein the molar ratio of dimethylglyoxime to polytetrahydrofuran is 1:1, and continuing the reaction for 3 to 4 hours.
6. The preparation method according to claim 2, characterized in that: The viscosity average molecular weight of the polyacrylic acid in step (3) is 450,000, 1.25 million or 4 million.
7. The preparation method according to claim 2, characterized in that: The polyacrylic acid-based cationic waterborne polyurethane binder system obtained in step (3) has a pH value of 5 to 6.
8. Use of the lithium ion battery negative electrode aqueous binder according to claim 1 in lithium ion batteries.
9. A lithium ion battery, characterized in that: The negative electrode material is Si / C, and the negative electrode material is bonded by the lithium ion battery negative electrode aqueous binder according to claim 1.
Citation Information
Patent Citations
Catechol-containing waterborne polyurethane / polyacrylic acid lithium battery negative electrode binder, preparation method thereof, battery negative electrode and secondary battery
CN118185517A
Cited By
Self-repairing conductive polymer adhesive, preparation method thereof and lithium ion battery
CN119775934A